Meta-analysis of health-related quality of life after minimally invasive versus open oesophagectomy for oesophageal cancer. Issue 9 (20th June 2017) - Kauppila, J H; Xie, S; Johar, A; Markar, S R; Lagergren, P
Abstract: Background: The aim of this systematic review and meta-analysis was to compare health-related quality of life (HRQoL) outcomes between minimally invasive and open oesophagectomy for cancer at different postoperative time points. Methods: A search of PubMed (MEDLINE), Web of Science, Embase, Scopus, CINAHL and the Cochrane Library was performed for studies that compared open with minimally invasive oesophagectomy. A random-effects meta-analysis was conducted for studies that measured HRQoL scores using the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 and QLQ-OES18 questionnaires. Mean differences (MDs) greater than 10 in scores were considered clinically relevant. Pooled effects of MDs with 95 per cent confidence intervals were estimated to assess statistical significance. Results: Nine studies were included in the qualitative analysis, involving 1157 patients who had minimally invasive surgery and 907 patients who underwent open surgery. Minimally invasive surgery resulted in better scores for global quality of life (MD 11·61, 95 per cent c.i. 3·84 to 19·39), physical function (MD 11·88, 3·92 to 19·84), fatigue (MD −13·18, −17·59 to −8·76) and pain (MD −15·85, −20·45 to −11·24) compared with open surgery at 3 months after surgery. At 6 and 12 months, no significant differences remained. Conclusion: Patients report better global quality of life, physical function, fatigue and pain 3 months after minimally invasive surgery compared with open surgery. No such differences remain at longer follow-up of 6 and 12 months. Abstract : Only different in short term